Draft Annual Plan 1987-88 Government of Himachal Pradesh - Planning Commission (Planning Commission, 1987)
Thus it would be seen that bulk of this population viz. 64.65 per cent are children in the age group years, 28.66 per cent in the age-group of 15-59 years and 6.69 percent in the age group of above 60 years The non-workers constitute 31.12 percent of labour force in the age-group of 15-59 years. Growth of State Economy: The estimates of State Domestic Product (SDP or State Income) is the most appropriate composite-economic indicator for measuring the general economic health of the State.
Government of Himachal Pradesh, Planning Department